Pursuit of Spiritual Happiness: Abu Hamid al-Ghazali on The Theory of Human Nature - Jarman Arroisi; Hamid Fahmy Zarkasyi; Iwan Aminur Rokhman; Fahrudin Mukhlis (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2023)
This article explores the philosophical and spiritual perspectives of Abu Hamid al-Ghazali, focusing on his views on the nature of humanity, the spiritual and material aspects of existence, and the pursuit of happiness Al-Ghazali's philosophy is deeply rooted in Islamic thought and draws upon the Quranic and Prophetic teachings.  Al-Ghazali posits that humans are composed of both a physical, ephemeral dimension (the material aspect) and an intellectual-transcendental dimension (the spiritual aspect). The article delves into al-Ghazali's classification of existence into two realms: the realm of decrees ('ālam al-amr) and the realm of creation ('ālam al-khalq). Human beings, according to al-Ghazali, embody both of these realms, with their physicality falling under the realm of creation and their spirituality under the realm of decree. Al-Ghazali introduces various terms to describe the spiritual entity within humans, such as al-‘aql (intellect), al-nafs (soul), al-qalb (heart), and al-rūh (spirit). He argues that while the body is material and earthly, the spirit is divine in origin and immortal.  The soul, as God's creation, reflects this governance by ruling over the body without being located in any specific physical part. It emphasizes that the spirit belongs to the realm of Divine decrees, making it distinct from material entities.  Al-Ghazali identifies different qualities within the human spirit, ranging from animalistic to angelic. He argues that the angelic quality, associated with the worship of God and the pursuit of Divine Beauty, represents the true essence of humanity. To attain happiness, individuals must purify themselves from worldly desires and base instincts.  The article underscores the importance of knowledge in al-Ghazali's philosophy, with knowledge being derived from God and serving as the criterion that separates humans from other creations. Knowledge enables individuals to understand their purpose, responsibilities, and the path to happiness.  The article explores al-Ghazali's perspective on happiness, highlighting his belief that it is primarily a spiritual and intellectual state. It emphasizes the significance of attaining knowledge of God for true happiness, as well as the importance of spiritual discipline and self-purification.